The paperboy - Pilkey, Dav, 1966- (New York : Orchard Books, 1996)
A paperboy and his dog enjoy the quiet of the early morning as they go about their rounds.
Wilson's Children, October 2006.
Elem. School Library Collection, June 2000.
School Library Journal starred, March 1996.
Notable/Best Books (A.L.A.), February 1997.
Five Owls, September 1996.
Booklist starred, March 1996.
Keywords: Newspaper carriers -- Fiction; Morning -- Fiction; African Americans -- Fiction; Caldecott honor book